Judicial independence & criticsms against the judiciary in Malaysia - Asril Amirul, Zakariah; Kamaliah, Salleh; Noor ‘Ashikin, Hamid (2016)
The judiciary is one of the vital governmental organs provided in a constitution of a country. Entrusted with the power to resolve disputes between the State and its citizen, or a citizen and another citizen, it is important that the judiciary must be independent from the other governmental organs i.e. the executive and the legislature. The purpose of this research is to explore the critics against the independency judiciary in Malaysia. To achieve the above purpose, this research examines the critics for and against judicial independence. The methodologies used in this qualitative research are library where relevant data from primary and secondary law documents were analysed. As a whole independence can only be won and secured by protecting the judiciary as a body and the members as to their office from scathing remarks and action from the public that may undermine the public's perception towards them.